Hydrometric Data Rescue in the Paraná River Basin. Issue 2 (2nd February 2018) - Antico, Andrés; Aguiar, Ricardo O.; Amsler, Mario L.
Abstract: The Paraná River streamflow is the third largest in South America and the sixth largest in the world. Thus, preserving historical Paraná hydrometric data is relevant for understanding South American and global hydroclimate changes. In this work, we rescued paper format data of daily Paraná water level observations taken uninterruptedly at Rosario City, Argentina, from January 1875 to present. The rescue consisted of the following activities: (i) imaging and digitization of paper format data, (ii) application of quality checks and homogeneity tests to the digitized water levels, and (iii) consideration of errors caused by gauge sinkings that may have occurred from 1875 to 1908. In addition, a rating curve was obtained for Rosario and it was used to convert water levels into discharges. The rescued water level observations and their associated discharge data provide the longest (last 143 years) continuous hydrometric records of the Paraná basin. The usefulness of these records was demonstrated by showing that the Paraná‐Pacific Ocean links observed after 1900 in previous studies are also evidenced in our nineteenth‐century discharge data. That is, high Paraná discharges coincided with El Niño events and with El Niño‐like states of the Interdecadal Pacific Oscillation (IPO), whereas low discharges coincided with La Niña events and with La Niña‐like IPO states. Key Points: We rescued historical hydrometric data of the Paraná River, one of the ten largest rivers in the world We offer the longest (last 143 years) continuous hydrometric records of the Paraná River The rescued data are valuable for studies of global and South American hydroclimate changes